2011
DOI: 10.1037/a0024047
|View full text |Cite
|
Sign up to set email alerts
|

Girls' math performance under stereotype threat: The moderating role of mothers' gender stereotypes.

Abstract: Previous research on stereotype threat in children suggests that making gender identity salient disrupts girls' math performance at as early as 5 to 7 years of age. The present study (n = 124) tested the hypothesis that parents' endorsement of gender stereotypes about math moderates girls' susceptibility to stereotype threat. Results confirmed that stereotype threat impaired girls' performance on math tasks among students from kindergarten through 2nd grade. Moreover, mothers' but not fathers' endorsement of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(102 citation statements)
references
References 46 publications
6
89
2
5
Order By: Relevance
“…Among the published articles, nonsignificant findings were almost always reported in an article along with some significant stereotype threat effects found either at another age (Ambady et al, 2001;Muzzatti & Agnoli, 2007), only with certain students (Keller, 2007), on certain items (Keller, 2007;Neuville & Croizet, 2007), or in certain contexts (Huguet & Regner, 2007, Study 2;Picho & Stephens, 2012;Tomasetto et al, 2011). Importantly, none of the three unpublished dissertations showed a stereotype threat effect.…”
Section: Summary Of Findings: Past Research and Current Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the published articles, nonsignificant findings were almost always reported in an article along with some significant stereotype threat effects found either at another age (Ambady et al, 2001;Muzzatti & Agnoli, 2007), only with certain students (Keller, 2007), on certain items (Keller, 2007;Neuville & Croizet, 2007), or in certain contexts (Huguet & Regner, 2007, Study 2;Picho & Stephens, 2012;Tomasetto et al, 2011). Importantly, none of the three unpublished dissertations showed a stereotype threat effect.…”
Section: Summary Of Findings: Past Research and Current Studiesmentioning
confidence: 99%
“…Neuville and Croizet (2007) found that stereotype threat had a negative effect on performance on difficult items but had a positive effect on easy items. Tomasetto et al (2011) found that girls whose mothers neither accepted nor rejected the gender stereotype about mathematics were susceptible to stereotype threat effects but girls whose mothers rejected the stereotype were not affected.…”
Section: Empirical Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parental perceptions, particularly those of mothers, are related to children's competence beliefs in mathematics, their future career choices and their susceptibility to the negative effects of stereotype threat (Bleeker & Jacobs, 2004;Jacobs, 1991;Tomasetto, Alparone, & Cadinu, 2011). Research has shown that teachers who report higher levels of MA are less confident about their mathematics teaching, are more likely to teach mathematics at a surface level, and to use less effective teaching methods (Brush, 1981;Gresham, 2009;Trujillo & Hadfield, 1999).…”
Section: Introductionmentioning
confidence: 99%